Evaluation of the Heavy Metal levels in Common Herbs and Spices Available on the Tripoli market by Atomic Absorption Spectrometer (Al-Farooq Journal of Sciences, 2026)
Herbs and spives are sources of many bioactive compounds that can improve the taste of food well as affect the digestion metabolism. Along with that they may also contain some substances as pesticides, heavy metals and which have harmful effect on the body.  In this work 14 of the most popularly spices and herb used in libya cuisine. were studied to determine Co, Cd, Pb, Zn, Se, Cu, As content in them. This was determied using atomic absorption spectrophotometry (AAS). Metals were found to be present in varied concentrations in the samples ,The results were compered with the safety standards of World health organization (WHO) and the Food Agricultural organization (FAO). The average concentration of  heavy metals as Cd detected ranged from 0.01 ppm – 1.04 ppm, Pb ranged from 0.59 – 4.63 ppm, Co in a range 0.05ppm – 0.2.20ppm, Zn ranged from 0.42ppm – 17.2ppm, concentration of Se was from 0.53ppm – 2.00ppm, Cu ranged from 2.02ppm – 14.3ppm, and As in a range 0.04ppm – 2.60 ppm The results obtained in this study indicate that spices and herbs used for food and meals seasoning may contain relatively high levels of toxic metals. therefore, like other food products they should be under continuous monitoring.
Keywords: Heavy metals, Herbs, Spices, Atomic absorption.